High-strength compression-resistant green recycled concrete and preparation method thereof

By using reinforcement agents such as water glass and nano-silicon carbide in recycled concrete, a silicic acid gel network system is formed, which solves the problem of low mechanical properties of recycled concrete, significantly improves compressive strength and density, and enhances the stability of concrete .

CN119490327APending Publication Date: 2025-02-21华东材料无锡有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411672415.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The mechanical properties of recycled concrete are low, mainly due to the fine cracks and pores generated by recycled coarse aggregates during mechanical crushing, which affects the strength and stability of the concrete.

Method used

By adding water glass to the concrete as a reinforcement, the surface of the water glass and the regenerated coarse aggregate produces a silica gel, which promotes the generation of cement hydration products, improves the bonding performance of the regenerated coarse aggregate, and combines nano silicon carbide and poly The use of acrylic fibers forms a fiber silica gel network system to enhance the mechanical properties of concrete.

Benefits of technology

It significantly improves the compressive strength and mechanical properties of recycled concrete, enhances the density and crack resistance of concrete, and improves the stability and service life of recycled concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146196780000071
    Figure BDA0005146196780000071
  • Figure BDA0005146196780000081
    Figure BDA0005146196780000081
Patent Text Reader

Abstract

The invention relates to high-strength compression-resistant green recycled concrete and a preparation method thereof, and relates to the technical field of concrete. The high-strength compression-resistant green recycled concrete is prepared from the following raw materials in parts by mass: 240 to 280 parts of cement, 80 to 100 parts of fly ash, 35 to 40 parts of slag, 640 to 680 parts of recycled coarse aggregate, 410 to 450 parts of fine aggregate, 44 to 52 parts of reinforcing agent, 7 to 9 parts of polycarboxylate superplasticizer and 200 to 240 parts of water. The reinforcing agent comprises water glass; the effect of improving the mechanical property of the concrete is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete technology, and in particular to a high-strength, compressive-resistant, green recycled concrete and a preparation process thereof. Background Art

[0002] Recycled concrete refers to new concrete made by crushing, cleaning, and grading discarded concrete, mixing it with grading in a certain proportion as recycled aggregate, partially or completely replacing natural aggregates such as sand and gravel (mainly coarse aggregate), and then adding cement, water, etc.

[0003] There will be old mortar residue on the surface of the recycled coarse aggregate, and the recycled aggregate will be subjected to greater external forces during the mechanical crushing process. A large number of fine cracks will easily appear inside the aggregate due to accumulated damage, thereby reducing the mechanical properties of the concrete. Summary of the invention

[0004] In order to improve the mechanical properties of concrete, the present application provides a high-strength, compressive-resistant green recycled concrete and a preparation process thereof.

[0005] In the first aspect, the present application provides a high-strength, compressive-resistant, green recycled concrete, which adopts the following technical solution: A high-strength, compressive-resistant green recycled concrete comprises the following raw materials in parts by mass: 240-280 parts of cement, 80-100 parts of fly ash, 35-40 parts of slag, 640-680 parts of recycled coarse aggregate, 410-450 parts of fine aggregate, 44-52 parts of reinforcing agent, 7-9 parts of polycarboxylate water reducer, and 200-240 parts of water; the reinforcing agent comprises water glass.

[0006] By adopting the above technical solution, adding water glass to concrete containing recycled coarse aggregate can improve the strength of concrete for the following reasons: Water glass and the surface of recycled coarse aggregate produce silica gel, which can react with calcium ions and aluminum ions produced by cement hydration to form hydrated calcium silicate or calcium aluminate, accelerating the hydration and coagulation of cement. The new hydration products not only increase the microcracks and pores of the recycled coarse aggregate, but also improve the bonding between the mortar on the surface of the recycled coarse aggregate and the new mortar, thereby improving the mechanical properties of the recycled concrete.

[0007] Preferably, the reinforcing agent further comprises nano-silicon carbide; the method for preparing the reinforcing agent comprises the following steps: mixing water glass and nano-silicon carbide, and stirring evenly to obtain the reinforcing agent.

[0008] By adopting the above technical solution and adding nano-silicon carbide to water glass for modification, the size of the water glass colloid can be made smaller, so that the water glass can more easily and evenly enter the pores of the mortar layer on the surface of the recycled coarse aggregate, thereby improving the strengthening effect of the water glass on the recycled coarse aggregate.

[0009] In addition, nano-silicon carbide can fill the gaps between cement particles, and nano-silicon carbide combines with free calcium hydroxide to form stable calcium carbosilicate hydrate, thereby increasing the density of concrete.

[0010] Preferably, the mass ratio of water glass to nano-silicon carbide is (32-36):1.

[0011] By adopting the above technical solution and controlling the mass ratio of nano-silicon carbide to water glass within the above range, the mechanical properties of water glass on recycled coarse aggregate can be effectively improved.

[0012] Preferably, 14-18 parts of polypropylene fibers are also included.

[0013] By adopting the above technical solution, polypropylene fibers can form a three-dimensional network structure in concrete, thereby filling the gaps in the concrete, reducing the voids, and enhancing the crack resistance of the concrete.

[0014] Moreover, nano-silicon carbide can undergo a secondary reaction with calcium ions, a cement hydration product, to generate hydrated calcium silicate gel, thereby improving the interfacial bonding strength between polypropylene fibers and the cement matrix, and thus the stability of the three-dimensional network structure in concrete.

[0015] Preferably, the polypropylene fiber is prepared by modification, and the modification preparation method of the polypropylene fiber comprises the following steps: The silane coupling agent is added to anhydrous ethanol, stirred evenly, and then the polypropylene fiber is added. After the reaction is completed, the polypropylene fiber is taken out, washed and dried to obtain modified polypropylene fiber.

[0016] By adopting the above technical solution, since the polypropylene fiber is hydrophobic and has poor bonding with concrete, cracks are formed between the polypropylene fiber and the cement mortar.

[0017] The surface roughness of polypropylene fiber can be increased by treating polypropylene fiber with silane coupling agent, thereby improving the interfacial adhesion between polypropylene fiber and cement mortar.

[0018] Moreover, the surface of the polypropylene fiber is covered with the polar groups of the silane coupling agent, thereby increasing the hydrophilicity of the polypropylene fiber, improving the wettability of the polypropylene fiber with cement mortar, increasing the interfacial bonding strength and compatibility, and thus reducing the pores and microcracks in the concrete system.

[0019] In addition, the silicon groups attached to the polypropylene fibers reacted with water molecules to form silanols. After multiple silanol molecules underwent polycondensation, they reacted with the hydroxyl groups on the surface of the cement mortar to form hydrogen bonds or covalent bonds, thereby strengthening the bonding force between the polypropylene fibers and the cement mortar.

[0020] Preferably, the mass ratio of the polypropylene fiber to the silane coupling agent is 1:(3.3-3.5).

[0021] By adopting the above technical solution and controlling the mass ratio of the polypropylene fiber to the silane coupling agent within the above range, the adhesion between the polypropylene fiber and the cement mortar can be effectively improved.

[0022] Preferably, the silane coupling agent is KH-550.

[0023] Preferably, 12-16 parts of expansive soil are also included.

[0024] By adopting the above technical solution and adding a proper amount of expansive soil into concrete, a micro-expansion effect can be produced to fill the tiny pores in the concrete, thereby increasing the density of the concrete and thus improving the mechanical properties of the concrete.

[0025] The silicate gel produced by the action of water glass is coated on the surface of the expansive soil. At the same time, the polypropylene fibers are interspersed between the expansive soils and connected with the silicate gel bonding membrane, and a fiber silicate gel network system is formed between the expansive soil and the silicate gel bonding membrane, which improves the density of the expansive soil, thereby improving the strength of the expansive soil, and further improving the positive effect of the addition of expansive soil to concrete on the mechanical properties of concrete.

[0026] Preferably, 9-11 parts of polyvinyl pyrrolidone are also included.

[0027] By adopting the above technical solution, polyvinyl pyrrolidone can be effectively coated on the surface of polypropylene fiber, and through its water-soluble properties, the hydrophilicity of polypropylene fiber is improved, which effectively helps to enhance the interfacial bonding strength between polypropylene fiber and cement mortar.

[0028] The hygroscopicity of polyvinyl pyrrolidone can help control the moisture content in expansive soil, reduce soil expansion and contraction caused by moisture changes, and thus improve the stability of concrete.

[0029] In a second aspect, the present application provides a method for preparing high-strength, compressive-resistant, green recycled concrete as in the first aspect, which adopts the following technical solution: A method for preparing high-strength compression-resistant green recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then a reinforcing agent and polycarboxylate water reducer are added, and stirring is continued to obtain recycled concrete.

[0030] In summary, the present application includes at least one of the following beneficial technical effects: 1. Water glass and the surface of recycled coarse aggregate produce silica gel, which can react with calcium ions and aluminum ions produced by cement hydration to form hydrated calcium silicate or calcium aluminate, accelerating the hydration and coagulation of cement. The new hydration products not only increase the microcracks and pores of the recycled coarse aggregate, but also improve the bonding between the mortar on the surface of the recycled coarse aggregate and the new mortar, thereby improving the mechanical properties of the recycled concrete.

[0031] 2. Treating polypropylene fibers with silane coupling agents can improve the roughness and hydrophilicity of the polypropylene fiber surface, thereby improving the interfacial adhesion between the polypropylene fibers and cement mortar. DETAILED DESCRIPTION

[0032] The present application discloses a high-strength, compressive, green recycled concrete and a preparation method thereof. The present application is further described in detail in combination with the embodiments and comparative examples. The raw materials involved in the present application can be obtained commercially, wherein polypropylene fiber is purchased from Shanghai Shuaishen Industrial Co., Ltd. and polyvinyl pyrrolidone is purchased from Hefei Tianjian Chemical Co., Ltd.

[0033] Example 1 The recycled concrete includes the following raw materials by weight: 260 g of cement, 90 g of fly ash, 38 g of slag, 660 g of recycled coarse aggregate, 430 g of fine aggregate, 48 g of reinforcing agent, 8 g of polycarboxylate water reducer, and 220 g of water.

[0034] The reinforcing agent includes water glass, and the water reducing rate of the polycarboxylate water reducer is 20%.

[0035] The preparation method of the enhancer comprises the following steps: The water glass and nano silicon carbide are mixed and stirred evenly to prepare a reinforcing agent.

[0036] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then a reinforcing agent and polycarboxylate water reducer are added, and stirring is continued to obtain recycled concrete.

[0037] Example 2 The recycled concrete includes the following raw materials by weight: 240 g of cement, 80 g of fly ash, 35 g of slag, 640 g of recycled coarse aggregate, 410 g of fine aggregate, 44 g of reinforcing agent, 7 g of polycarboxylate water reducer, and 200 g of water.

[0038] The reinforcing agent includes water glass and nano silicon carbide, and the mass ratio of water glass to nano silicon carbide is 32:1; the water reducing rate of the polycarboxylic acid water reducer is 20%.

[0039] The preparation method of the enhancer comprises the following steps: The water glass and nano silicon carbide are mixed and stirred evenly to prepare a reinforcing agent.

[0040] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then a reinforcing agent and polycarboxylate water reducer are added, and stirring is continued to obtain recycled concrete.

[0041] Example 3 The recycled concrete includes the following raw materials by weight: 280 g of cement, 100 g of fly ash, 40 g of slag, 680 g of recycled coarse aggregate, 450 g of fine aggregate, 52 g of reinforcing agent, 9 g of polycarboxylate water reducer, and 240 g of water.

[0042] The reinforcing agent includes water glass and nano silicon carbide, and the mass ratio of water glass to nano silicon carbide is 36:1; the water reducing rate of the polycarboxylic acid water reducer is 20%.

[0043] The preparation method of the enhancer comprises the following steps: The water glass and nano silicon carbide are mixed and stirred evenly to prepare a reinforcing agent.

[0044] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then a reinforcing agent and polycarboxylate water reducer are added, and stirring is continued to obtain recycled concrete.

[0045] Example 4 The recycled concrete includes the following raw materials by weight: 260 g of cement, 90 g of fly ash, 38 g of slag, 660 g of recycled coarse aggregate, 430 g of fine aggregate, 48 g of reinforcing agent, 8 g of polycarboxylate water reducer, and 220 g of water.

[0046] The reinforcing agent includes water glass and nano silicon carbide, and the mass ratio of water glass to nano silicon carbide is 34:1; the water reducing rate of the polycarboxylic acid water reducer is 20%.

[0047] The preparation method of the enhancer comprises the following steps: The water glass and nano silicon carbide are mixed and stirred evenly to prepare a reinforcing agent.

[0048] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then a reinforcing agent and polycarboxylate water reducer are added, and stirring is continued to obtain recycled concrete.

[0049] Example 5 The difference between Example 5 and Example 4 is that the mass ratio of water glass to nano-silicon carbide is 30:1.

[0050] Example 6 The difference between Example 6 and Example 4 is that the mass ratio of water glass to nano-silicon carbide is 38:1.

[0051] Example 7 The difference between Example 7 and Example 4 is that the concrete further includes 14 g of polypropylene fibers.

[0052] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly. Then, a reinforcing agent, polycarboxylate water reducer and polypropylene fiber are added, and stirring is continued to obtain recycled concrete.

[0053] Example 8 The difference between Example 8 and Example 7 is that the concrete further includes 18 g of polypropylene fibers.

[0054] Example 9 The difference between Example 9 and Example 7 is that the concrete further includes 16 g of polypropylene fibers.

[0055] Example 10 The difference between Example 10 and Example 9 is that the polypropylene fiber is prepared by modification, and the modification preparation method of the polypropylene fiber comprises the following steps: Add 33g of silane coupling agent to 120g of anhydrous ethanol, stir evenly, then add 10g of polypropylene fiber, soak for 30 minutes, take out the soaked polypropylene fiber, wash it with clean water, and then put it into a 100°C drying oven for 2 hours to obtain modified polypropylene fiber.

[0056] The silane coupling agent is KH-550.

[0057] Embodiment 11 The difference between Example 11 and Example 9 is that the polypropylene fiber is prepared by modification, and the modification preparation method of the polypropylene fiber comprises the following steps: Add 35g of silane coupling agent to 120g of anhydrous ethanol, stir evenly, then add 10g of polypropylene fiber, soak for 30 minutes, take out the soaked polypropylene fiber, wash it with clean water, and then put it into a 100°C drying oven to dry for 2 hours to obtain modified polypropylene fiber.

[0058] The silane coupling agent is KH-550.

[0059] Example 12 The difference between Example 12 and Example 9 is that the polypropylene fiber is prepared by modification, and the modification preparation method of the polypropylene fiber comprises the following steps: Add 34g of silane coupling agent to 120g of anhydrous ethanol, stir evenly, then add 10g of polypropylene fiber, soak for 30 minutes, take out the soaked polypropylene fiber, wash it with clean water, and then put it into a 100°C drying oven for 2 hours to obtain modified polypropylene fiber.

[0060] The silane coupling agent is KH-550.

[0061] Embodiment 13 The difference between Example 13 and Example 12 is that the mass ratio of the polypropylene fiber to the silane coupling agent is 1:3.1.

[0062] Embodiment 14 The difference between Example 14 and Example 12 is that the mass ratio of the polypropylene fiber to the silane coupling agent is 1:3.7.

[0063] Embodiment 15 The difference between Example 15 and Example 12 is that the concrete also includes 12 g of expansive soil.

[0064] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly. Then, a reinforcing agent, polycarboxylate water reducer, polypropylene fiber and expansive soil are added, and stirring is continued to obtain recycled concrete.

[0065] Example 16 The difference between Example 16 and Example 15 is that the concrete also includes 16 g of expansive soil.

[0066] Embodiment 17 The difference between Example 17 and Example 15 is that the concrete also includes 14 g of expansive soil.

[0067] Embodiment 18 The difference between Example 18 and Example 17 is that the concrete further includes 9 g of polyvinyl pyrrolidone.

[0068] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then reinforcing agent, polycarboxylic acid water reducer, polypropylene fiber, expansive soil, polyvinyl pyrrolidone are added, and stirring is continued to obtain recycled concrete.

[0069] Embodiment 19 The difference between Example 19 and Example 18 is that the concrete further includes 11 g of polyvinyl pyrrolidone.

[0070] Embodiment 20 The difference between Example 20 and Example 18 is that the concrete further includes 10 g of polyvinyl pyrrolidone.

[0071] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the recycled concrete does not contain a reinforcing agent.

[0072] The method for preparing recycled concrete comprises the following steps: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then polycarboxylate water reducer is added, and stirring is continued to obtain recycled concrete.

[0073] Performance testing: Sampling: The concrete prepared in Examples 1-20 and Comparative Example 1 was taken as test samples, and after curing for 28 days, the test was performed. The test samples were standard cubic specimens of 150 mm × 150 mm × 150 mm.

[0074] Strength performance test: Test the compressive strength of the sample in accordance with GB / T50081-2019 "Standard method for test methods of physical and mechanical properties of concrete", and record the test results in Table 1.

[0075] Table 1 Data analysis Specifically combining the test results of Examples 2-4 and Example 1, the compressive strength of Example 2-4 is higher than that of Example 1, and the analysis is as follows: The difference between Example 2-4 and Example 1 is that the reinforcing agent also includes nano-silicon carbide. On the one hand, nano-silicon carbide can make the size of the water glass colloid smaller, and on the other hand, nano-silicon carbide can fill the gaps between cement particles, and nano-silicon carbide combines with free calcium hydroxide to form a stable calcium carbosilicate hydrate, thereby improving the density of the concrete, and then improving the mechanical properties of the concrete.

[0076] Specifically combining the test results of Examples 7-9 and Example 4, the compressive strength of Examples 7-9 is higher than that of Example 4, and the analysis is as follows: The difference between Examples 7-9 and Example 4 is that polypropylene fibers can form a three-dimensional network structure in concrete, and nanosilicon carbide can react with calcium ions, a cement hydration product, to generate hydrated calcium silicate gel, which improves the stability of the three-dimensional network structure in concrete, thereby improving the mechanical properties of concrete.

[0077] Specifically combining the test results of Examples 10-12 and Example 9, the compressive strength of Examples 10-12 is higher than that of Example 9. The analysis is as follows: the difference between Examples 10-12 and Example 9 is that the silane coupling agent improves the hydrophilicity of the polypropylene fiber, and the silicon groups attached to the polypropylene fiber react with water molecules to generate silanols. After the silanol molecules undergo a condensation reaction, they react with the hydroxyl groups on the surface of the cement mortar to form hydrogen bonds or covalent bonds, thereby strengthening the bonding force between the polypropylene fiber and the cement mortar, thereby improving the mechanical properties of the concrete.

[0078] Specifically combining the test results of Examples 15-17 and Example 12, the compressive strength of Examples 15-17 is higher than that of Example 12. The analysis is as follows: the difference between Examples 15-17 and Example 12 is that the expansive soil can produce a micro-expansion effect, fill the tiny pores in the concrete, and improve the density of the concrete. In addition, the silicate gel produced by the action of water glass is coated on the surface of the soil particles, and at the same time, the polypropylene fibers are interspersed between the expansive soils and connected with the silicate gel bonding film, and a fiber silicate gel network system is formed between the soil particles and the silicate gel bonding film, which improves the density of the expansive soil and thus improves the mechanical properties of the concrete.

[0079] Specifically combining the test results of Examples 18-20 and Example 17, the compressive strength of Examples 18-20 is higher than that of Example 17. The analysis is as follows: the difference between Examples 18-20 and Example 17 is that polyvinyl pyrrolidone improves the hydrophilicity of polypropylene fibers, and the hygroscopicity of polyvinyl pyrrolidone can help control the moisture content in expansive soil, reduce soil expansion and contraction caused by moisture changes, thereby improving the mechanical properties of concrete.

[0080] Specifically combining the test results of Example 1 and Comparative Example 1, the compressive strength of Example 1 is higher than that of Comparative Example 1. The analysis is as follows: the difference between Example 1 and Comparative Example 1 is that water glass and the surface of the recycled coarse aggregate produce silicate gel, and the silicate gel can react with the cement hydration product to generate hydrated calcium silicate or calcium aluminate, which not only improves the microcracks and pores of the recycled coarse aggregate, but also improves the bonding between the mortar on the surface of the recycled coarse aggregate and the new mortar, thereby improving the mechanical properties of the concrete.

[0081] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A high-strength, compressive-resistant green recycled concrete, characterized by: The invention comprises the following raw materials in parts by weight: 240-280 parts of cement, 80-100 parts of fly ash, 35-40 parts of slag, 640-680 parts of recycled coarse aggregate, 410-450 parts of fine aggregate, 44-52 parts of reinforcing agent, 7-9 parts of polycarboxylic acid water reducer and 200-240 parts of water; the reinforcing agent comprises water glass.

2. The high-strength, compressive-resistant green recycled concrete according to claim 1, characterized in that: The reinforcing agent further comprises nano silicon carbide; and the preparation method of the reinforcing agent comprises the following steps: The water glass and nano silicon carbide are mixed and stirred evenly to prepare a reinforcing agent.

3. The high-strength, compressive-resistant green recycled concrete according to claim 2, characterized in that: The mass ratio of the water glass to nano-silicon carbide is (32-36):

1.

4. The high-strength, compressive-resistant green recycled concrete according to claim 2, characterized in that: Also included are 14-18 parts of polypropylene fibers.

5. The high-strength, compressive-resistant green recycled concrete according to claim 5, characterized in that: The polypropylene fiber is prepared by modification, and the modification preparation method of the polypropylene fiber comprises the following steps: The silane coupling agent is added to anhydrous ethanol, stirred evenly, and then the polypropylene fiber is added. After the reaction is completed, the polypropylene fiber is taken out, washed and dried to obtain modified polypropylene fiber.

6. The high-strength, compressive-resistant green recycled concrete according to claim 5, characterized in that: The mass ratio of the polypropylene fiber to the silane coupling agent is 1:(3.3-3.5).

7. The high-strength, compressive-resistant green recycled concrete according to claim 5, characterized in that: The silane coupling agent is KH-550.

8. The high-strength, compressive-resistant green recycled concrete according to claim 1, characterized in that: Also include 12-16 parts of expansive soil.

9. The high-strength, compressive-resistant green recycled concrete according to claim 1, characterized in that: Also included are 9-11 parts of polyvinyl pyrrolidone.

10. A method for preparing high-strength compressive green recycled concrete as claimed in claim 1, characterized in that: The steps include: The cement, fly ash, slag and water are mixed evenly, and then recycled coarse aggregate and fine aggregate are added, and stirred evenly, and then a reinforcing agent and polycarboxylate water reducer are added, and stirring is continued to obtain recycled concrete.